Fundraising Strategy of Zakat, Infaq, Sadaqah and Waqf Funds of the National Amil Zakat Institution Daarut Tauhiid Peduli Riau - Alfalah, Bahari; Sanshia Arum, Hafidza (JAWI : Journal of Ahkam Wa Iqtishad, 2024)
The large number of amil zakat institutions in Indonesia makes it a new problem for zakat management organizations or OPZ, making it a lot of options for people who will distribute their zakat. The success of an institution in managing zakat funds depends on the amount of zakat funds to be obtained. This study aims to find out how the strategy used by the National Amil Zakat Institute Daarut Tauhiid Peduli Riau in collecting zakat funds, infak alms and waqf. This study uses a qualitative research method that involves direct access to the research location to collect data related to the research title. With data collection techniques using observation, interviews, and documentation of the National Amil Zakat Institution Daarut Tauhiid Peduli Riau as a research informant. The fundraising strategy for zakat, infaq, alms and waqf funds carried out by the National Amil Zakat Institution Daarut Tauhiid Peduli Riau is the first, the identification of muzakki segments and targets which can be said to be the beginning of the strategy used in fundraising, the second is to gain the trust of muzakki which is a priority by the institution, the third is to build a communication system that must always be paid attention to by the institution because it still has shortcomings in terms of staff and others so on, and the fourth is to arrange and carry out services which is an effort that is always paid attention to by the amil zakat institution, especially the National Amil Zakat Institution Daarut Tauhiid Peduli Riau.